Eco-friendly polydimethylsiloxane-based self-supporting film containing europium-polyoxometalate: A flexible luminescent material for white light generation - Simoes, Mateus Batista; Ullah, Sajjad [UNESP]; Hazra, Chanchal [UNESP]; Man, Michel Wong Chi; Lima Ribeiro, Sidney Jose [UNESP]; Rodrigues-Filho, Ubirajara Pereira (Elsevier B.V., 2018)
Lanthanide (Ln(3+))-doped suitable matrices exhibit unique luminescent properties which are important for applications in optoelectronic devices. Most of the Ln(3+)-based luminescent materials are, however, prepared in powder form using suitable robust inorganic host matrices. These matrices, often, experience lack of flexibility which is important for many applications such as LEDs and wearable devices, among others. To address this aspect, we report the preparation of flexible and highly transparent luminescent membranes based on poly-dimethylsiloxane- hydroxyurethanes (PDMSUr) as the hybrid framework and Europium-polyoxometalate (Eu (PW11)(2)) complex as the luminescent component. The PDMSUr, besides acting as green, transparent and flexible matrix, is found to increase the emission decay lifetime (from 1.5 ms to 3.0 ms) when Eu(PW11)(2) is incorporated in the hybrid matrix. Moreover, upon UV excitation, the matrix exhibits a broader emission around 450 nm which, together with the characteristic emission of Eu3+ ions, leads to the generation of white light.
Keywords: Lanthanide; Hybrid matrix; Polyhydroxyurethane; White light